Reconstructing the Enforcement of Women's Financial Rights After Divorce in Indonesia's Religious Courts: Structural Barriers and an Aswaja-Based Substantive Justice Approach - Abdul Kamid; Bahrul Fawaid (Lembaga Bale Literasi, 2026)
The protection of women’s financial rights after divorce remains a significant issue within the Islamic family law system in Indonesia. Various legal regulations have recognized the rights of former wives to receive iddah maintenance, mut’ah, child support, and other economic entitlements. However, such normative recognition has not always been accompanied by the actual fulfillment of these rights, as a considerable gap persists between court decisions and their implementation. This study aims to analyze the legal construction of women’s post-divorce financial rights, the implementation of judicial decisions, the structural obstacles affecting the effectiveness of rights enforcement, and to formulate a model for strengthening rights enforcement based on Ahlussunnah wal Jama’ah (Aswaja) principles and substantive justice. This research employs a normative-empirical legal method with statutory, conceptual, case, and empirical approaches. Data were collected through literature review, court decision analysis, interviews, and documentation. The findings reveal that the main obstacles include weaknesses in execution regulations, limited judicial authority, the absence of an asset-tracing system, high execution costs, low legal awareness, unequal bargaining positions of women, economic constraints, and patriarchal cultural influences. This study proposes an Aswaja- and Substantive Justice-Based Model for the Enforcement of Women’s Financial Rights, emphasizing preventive measures, monitoring, enforcement, and recovery of rights to achieve a more effective, equitable, and sustainable legal protection system.